The Effect of Interest Rate Changes on the Common Stock Returns of Financial Institutions - Flannery, Mark J.; James, Christopher M. (Journal of Finance, 1984)
This paper examines the relation between the interest rate sensitivity of common stock returns and the maturity composition of the firm's nominal contracts. Using a sample of actively traded commerical banks and stock savings and loan associations, common stock returns are found to be correlated with interest rate changes. The co-movement of stock returns and interest rate changes is positively related to the size of the maturity difference between the firm's nominal assets and liabilities.